‘The visible renewal of human life’: Barth's ethical assessment of the Reformed confessions - Allen, R. Michael (Scottish journal of theology, 2024)
Karl Barth's Theology of the Reformed Confessions characterised those catechetical texts as more ethical in orientation and more horizontal in focus than the corresponding Lutheran symbols. By examining both primary and secondary sources, this paper shows that while Barth legitimately illumines a key element of the Reformed witness regarding a connection between faith and life, his polemical eye may also distort his perspective on its distinctiveness, likely owing to contextual factors related to his self-fashioning a Reformed identity in his early academic service at the predominantly Lutheran University of Göttingen and alongside his colleague, Emanuel Hirsch.